Learner-Controlled Self-Observation is Advantageous for Motor Skill Acquisition - Ste-Marie, Diane M.; Vertes, Kelly A.; Law, Barbi; Rymal, Amanda M. (Frontiers in Psychology, 2013)
There were two main objectives of this research. First, we wanted to examine whether video feedback of the self (self-observation) was more effective for motor skill learning when the choice to view the video was provided to the learner (learner-controlled; LC) as opposed to an experimenter-controlled (EC) delivery. Secondly, we explored whether there were differences in the self-regulatory processes of self-efficacy and intrinsic motivation, as well as perceived choice between the LC and EC conditions. Two groups (LC and EC) of children (M age of 11.2 years; SD = 1.89) attempted to learn a progression of trampoline skills during a two-day acquisition phase in which video self-observation was available. The second acquisition day was followed by a no self-observation retention test one day later. It was hypothesized that, during retention, the LC group would be more self-efficacious about their ability to progress through the trampoline skills, show greater intrinsic motivation and perceived choice, and go further in skill progression than the EC group. Analysis of the acquisition data showed the LC group had greater increases in self-efficacy as compared to the EC group. Results of the retention test showed that the participants in the LC group obtained higher scores on the intrinsic motivation and perceived choice measures and had higher skill progression scores as compared to the EC group. Regression analysis showed that group assignment and self-efficacy were significant predictors of the physical performance benefits noted in retention. These findings are discussed within Zimmerman’s (2004) self-regulation of learning model.